ANALYSIS OF HUMAN RESOURCES DEVELOPMENT IN YDSF SURABAYA ON ISLAMIC ECONOMIC PERSPECTIVE - Syamsuri, Syamsuri; Harahap, Soritua Ahmad Ramdani (Universitas Negeri Surabaya, 2019)
This study aims to analyze the role of human resource development in developing the people's economy through social institutions. By using qualitative methods and collecting data through observation, interviews and documentation at the Al-Falah Social Fund Foundation (YDSF) Surabaya as a research sample. The results of the study explain that the development of human resources at the Al-Falah Surabaya Social Fund Foundation uses a spiritual and material approach. Through these two approaches, human resource development works with programs that aim to improve human resources both spiritually and materially. In addition, this article also explains the obstacles faced and their solutions to be implemented by the Surabaya Al Falah Social Fund Foundation in order to optimize the quality of HR.